2024
DOI: 10.1136/bmjopen-2023-080160
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing implementation and sustainability of interventions to improve oral health and related health behaviours in adults experiencing severe and multiple disadvantage: a mixed-methods systematic review

Deepti A John,
Emma A Adams,
Laura J McGowan
et al.

Abstract: ObjectivesAmong people experiencing severe and multiple disadvantage (SMD), poor oral health is common and linked to smoking, substance use and high sugar intake. Studies have explored interventions addressing oral health and related behaviours; however, factors related to the implementation of these interventions remain unclear. This mixed-methods systematic review aimed to synthesise evidence on the implementation and sustainability of interventions to improve oral health and related health behaviours among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…A systematic review of the global literature was conducted as part of our project to identify evidence on the implementation and sustainability of health interventions to improve oral health and related health behaviours in people experiencing SMD. 21 This review reflects the findings of the present paper and finds moderate evidence that trust, resources and motivation levels are required to improve the implementation and sustainability of health interventions. Similarly, our findings related to training for staff were also found in a previous study that reported that 'challenging behaviour', of service users, often as a result of underlying social and health issues of people with SMD, can be a barrier in delivering the intervention.…”
Section: Discussionsupporting
confidence: 69%
“…A systematic review of the global literature was conducted as part of our project to identify evidence on the implementation and sustainability of health interventions to improve oral health and related health behaviours in people experiencing SMD. 21 This review reflects the findings of the present paper and finds moderate evidence that trust, resources and motivation levels are required to improve the implementation and sustainability of health interventions. Similarly, our findings related to training for staff were also found in a previous study that reported that 'challenging behaviour', of service users, often as a result of underlying social and health issues of people with SMD, can be a barrier in delivering the intervention.…”
Section: Discussionsupporting
confidence: 69%